Tingkat Depresi dan Faktor yang Mempengaruhi pada Pasien Kanker Serviks di RSUD Dr. Soetomo - Devana Nuur Raihan; Brahmana Askandar Tjokroprawiro; Agustina Konginan (Journal of Health (JoH), 2022)
Cancer patients in Indonesia experience mild to severe depression around 34.4% which can affect their quality of life. The study aimed to determine the distribution of depression in cervical cancer patients, the level of depression that predominated in cervical cancer patients, and the relationship between the level of depression in cervical cancer and the influencing factors in cervical cancer patients RSUD Dr. Soetomo. The research design used descriptive-analytic with a research population of 2845 people. The research sample was determined using a descriptive formula and was taken in September 2021 from outpatients at the Poli Onkologi Satu Atap (POSA), who was diagnosed with cervical cancer were 45 people by distributing questionnaires containing BDI-II and Holmes and Rahe Scale instruments. The sampling technique used non-probability sampling with the purposive sampling technique. Analytical descriptive data analysis using Chi-square test. The results showed that the majority had mild depression as many 21 respondents (46.7%), followed by minimal depression as many 19 respondents (42.2%), moderate depression as many three respondents (6.7%), and severe depression as many two respondents (4.4%). The relationship between the level of depression with influencing factors was found to be significant in the number of marriages. The second marriage does not always show better results than the first marriage, the fear of repeated marriage failures and the emergence of conflicts in the future can potentially lead to depression. Women with second marriages have higher rates of depression. In the relationship between depression and other factors, namely age, last education, marital status, monthly income, cervical cancer stage, family history of cervical cancer, and duration of diagnosis, did not have a significant relationship.